The Effectiveness of Online English Learning Activities in Rural Area: A Case Study of Timpag Village, Tabanan, Bali - I Wayan Kiki Sanjaya; I Putu Ryan Dharma Putra; I Gede Mudana; Budi Susanto (Bali Membangun Bali: Jurnal Bappeda Litbang, 2022)
Purpose: This research aims to analyze online English learning activities in the rural area of Bali through a case study of Timpag Village, Tabanan Regency, Bali. Design/methodology/approach: A SWOT analysis was conducted to determine the strengths, weaknesses, opportunities, and threats that influence the decline in student enthusiasm related to online learning. Findings: The results obtained are a declining trend in teaching and learning activities in Timpag Village due to less interactive learning material and the lack of interaction between parents and teachers in monitoring student learning activities at home. Implications: The solution given is to improve coordination between parents and teachers and improve the quality of the material that will be provided.